The Influence of Risk Preference and Financial Condition on Tax Compliance of Boarding House Tax in Banjarmasin - Anuar Syahdan, Saifhul; Abdul Rahman, Rahayu; Nastiti, Rizky; Ruwanti, Gemi; Norbaiti, Norbaiti (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2022)
This study aims to examine the effect of risk preference and financial condition on tax compliance of boarding house owners. The variables of this study are tax compliance, risk preference and financial condition. This study used primary data obtained from the questionnaire. In addition, the respondents of this study were the taxpayers who owned a boarding house in Banjarmasin chosen by using purposive sampling. Furthermore, multiple regression analysis was employed to analyze the obtained data. The results of the study concluded that risk preference and financial condition had positive effect on tax compliance.